1995
DOI: 10.1016/s0022-5223(95)70354-3
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic cardiac transplantation: A comparison of standard and bicaval Wythenshawe techniques

Abstract: We describe an alternative technique for orthotopic cardiac transplantation (bicaval Wythenshawe technique), which maintains the right and left atrial anatomy. We compared the new bicaval technique with the conventional (Lower and Shumway) technique of orthotopic cardiac transplantation to identify any beneficial physiologic and clinical outcomes resulting from maintaining the normal anatomy. Seventy-five patients were randomized on an alternate basis to two groups: group A (n = 40) had orthotopic cardiac tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 23 publications
4
54
1
4
Order By: Relevance
“…[17] In two randomized trials, permanent pacing was not required in any patients undergoing bicaval anastomosis, but in five (6.7%) of 75 patients undergoing biatrial anastomosis. [18,19] Our cohort was comprised of those undergoing biatrial orthotopic heart transplantation, and our results are in consistent with the literature data.…”
Section: Discussionsupporting
confidence: 84%
“…[17] In two randomized trials, permanent pacing was not required in any patients undergoing bicaval anastomosis, but in five (6.7%) of 75 patients undergoing biatrial anastomosis. [18,19] Our cohort was comprised of those undergoing biatrial orthotopic heart transplantation, and our results are in consistent with the literature data.…”
Section: Discussionsupporting
confidence: 84%
“…Entretanto, como demonstrado anteriormente em trabalho desta Instituição (29) e em outros relatos (30)(31)(32) , na técnica bicaval é menor a incidência de taquiarritmias e o uso de marcapasso definitivo, bem como é menor o índice de regurgitação mitral ou tricúspide (25,33) . Na nossa casuística, não temos nenhum paciente que necessitou de marcapasso definitivo após a técnica bicaval/bipulmonar, enquanto que há um após a técnica atrial.…”
Section: Gráfico 10unclassified
“…El-Gamel et al (18) stated that in their 85 patient working groups, with the bicaval technique the right atrial pressure was lower, the atrial tachyarrhythmia was encountered less, the mitral incompetence was less and the diuretic dose need was less. Cui et al (19) in their studies reported that in the patients in which the biatrial anastomosis technique is used, the atrial flutter incidence was significantly high but the atrial fibrillation was similar in both technique.…”
Section: Variablesmentioning
confidence: 99%